Eksplorasi Peran Logam Transisi (Fe, Cu, Mn) dalam Sintesis In-situ dan Pertumbuhan Kristal Zeolit Aluminofosfat: Analisis Struktural dan Termal - Muhammad Fadil Athar; Siti Khumaira; Ahmad Fahrizal (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to explore the role of transition metals (Fe, Cu, Mn) in the in-situ synthesis and crystal growth of aluminophosphate zeolites through structural and thermal analysis approaches. Crystal structure modification was carried out by incorporating transition metal cations into the aluminophosphate framework to observe their effects on morphology, pore distribution, thermal stability, and potential catalytic properties. The synthesis process was conducted using the hydrothermal method with varying metal concentrations, followed by characterization through XRD, FTIR, SEM, EDX, and thermal analysis (TGA/DSC). The results show that the presence of Fe, Cu, and Mn plays a significant role in directing crystal growth with distinct patterns. Fe enhances framework ordering and improves thermal stability, Cu influences crystal size and surface properties, while Mn contributes to the formation of framework defects that increase the specific surface area. Overall, transition metal doping improves the structural properties and enhances the catalytic potential of aluminophosphate zeolites in oxidation reactions and biomass conversion. These findings contribute to the fundamental understanding of aluminophosphate-based porous material synthesis as well as opportunities for their development in environmentally friendly industrial applications.